World Experience in the Use of Cash and in-Kind Transfers in Social Security (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article presents opinions on the foreign experience of social security, which plays an important role in improving the standard of living of the population. The article presents the world models of social protection and their review. In particular, the article describes the continental, Anglo-Saxon and Scandinavian models.